Descentralização da função de compras e licitações: o caso da Universidade Federal de São Carlos (UFSCar) - Silva, Rogério Colaço da (2016)
The Federal University of São Carlos is part of the current period of expansion of courses and vacancies in the Federal Institutions of Higher Education (IFES), especially after REUNI (Support Program Plan of Restructuring and Expansion of Federal Universities). In order to meet the demand of a growing institution, took effect several administrative changes. One of the changes underway is the implementation of decentralized units of shopping, which is the object of study. This research has the following objectives: identify the factors inherent to this process (steps, difficulties, solutions, benefits, etc.), as well as the impacts of the changes made in the organizational structure generated in the administration of the University, map the new organizational structure Dean of administration (PROAD), identify problems and propose solutions and changes in procedures that may assist in the execution of decentralized purchasing activity. To this end, research is proposed as an action research with qualitative approach with exploratory way, designed as a single case study, the Federal University of São Carlos (UFSCar).